2016
DOI: 10.18632/oncotarget.13495
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the acylphosphatase 2 gene and the risk of breast cancer in a Han Chinese population

Abstract: We performed a case-control study to investigate the associations between seven single nucleotide polymorphisms (SNPs) in the acylphosphatase 2 (ACYP2) gene and breast cancer (BC) risk in a Han Chinese population. There were 183 BC cases and 195 healthy controls included in the study. The SNPs were genotyped using the Sequenom MassARRAY platform. Logistic regression (adjusted for age group, body mass index [BMI], and menopause status), was used to evaluate the associations between the various genotypes and BC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In addition to these association studies, many metaanalyses have been conducted to increase statistical power, to resolve conflicting results between individual studies, and to improve estimates of the size of the effect (Hunter and Schmidt, 1990). The results have demonstrated consistency, with all seven SNPs shown to be significantly associated with an increased risk of breast cancer among different ethnic groups, including Asians and Europeans, with P values lower than 0.03 and OR (95% CI) values ranging from 1.07 (1.01 -1.13) to 1.62 (1.44 -1.83) (Wang et al, 2013;Zheng et al, 2014;Tang et al, 2016;Wang et al, 2016;Yang et al, 2016;Zhang et al, 2016;Hu et al, 2017). Interestingly, two SNPs, rs889312 and rs13281615, were shown not to be associated with breast cancer risk in Africans (Zheng et al, 2014;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition to these association studies, many metaanalyses have been conducted to increase statistical power, to resolve conflicting results between individual studies, and to improve estimates of the size of the effect (Hunter and Schmidt, 1990). The results have demonstrated consistency, with all seven SNPs shown to be significantly associated with an increased risk of breast cancer among different ethnic groups, including Asians and Europeans, with P values lower than 0.03 and OR (95% CI) values ranging from 1.07 (1.01 -1.13) to 1.62 (1.44 -1.83) (Wang et al, 2013;Zheng et al, 2014;Tang et al, 2016;Wang et al, 2016;Yang et al, 2016;Zhang et al, 2016;Hu et al, 2017). Interestingly, two SNPs, rs889312 and rs13281615, were shown not to be associated with breast cancer risk in Africans (Zheng et al, 2014;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 79%
“…Among the genotyped SNPs, five (rs1219648, rs3817198, rs889312, rs10941679 and rs13281615) were found to not show an association with breast cancer risk, but the remaining two (rs2046210 and rs3803662) showed a strong association with the risk of breast cancer in our Vietnamese population cohort. In the literature, five SNPs (rs1219648, rs3817198, rs889312, rs10941679, and rs13281615) were shown to be strongly associated with breast cancer risk in Europeans and Asians (Antoniou et al, 2009;Shan et al, 2012;Wang et al, 2013;Sawyer et al, 2014;Siddiqui et al, 2014;Campa et al, 2015;Ghoussaini et al, 2016;Mazhar et al, 2016;Tang et al, 2016;Zhang et al, 2016;Hein et al, 2017), as well as in populations similar to the Vietnamese, namely Chinese and Taiwanese populations (Liang et al, 2008;Long et al, 2010;Zheng et al, 2010;Kuo et al, 2017). Furthermore, among these populations, these five SNPs have been shown to be associated with an increased risk of breast cancer with the highest OR (95% CI) of 3.06 (1.79-5.25).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, three studies have replicated this association with cisplatin-induced hearing loss in 156 osteosarcoma patients (41), 149 pediatric cancer patients (42), and 229 testicular cancer patients (43). ACYP2 encodes for an enzyme that catalyzes phosphate hydrolysis in membrane pumps, most notably the Ca 2þ /Mg 2þ ATPase from the sarcoplasmic reticulum of skeletal muscle (44). Importantly, ACYP2 is expressed in the cochlea for ATP-dependent Ca 2þ signaling that is critical for hair cell development and has been directly implicated in hair cell damage (45,46), providing a rationale for its association with CAO.…”
Section: Ototoxicitymentioning
confidence: 99%
“…The study found that ACYP2 is associated with a variety of tumors or diseases, such as lung cancer (Chen et al, ), colorectal cancer (Liu et al, ), breast cancer (Zhang et al, ), stroke (Liang et al, ), high altitude pulmonary edema (He et al, ). Cui et al researched the influence of telomere related genes on the prognosis of glioma, found that ACYP2 rs843720 influence the overall survival rate, the overall survival rate of glioma patients with mutated genotype was lower than that of wild‐type patients (Cui et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al recruited 1,156 participants, assessed the relationship between ACYP2 gene polymorphism and lung cancer, and revealed that rs1682111 (A/T) and rs843720 (G/T) in ACYP2 gene promoted the risk of lung cancer (Chen et al, ). At the same time, for breast cancer, Zhang et al research the influence of ACYP2 gene polymorphism on breast cancer by 183 cases and 195 controls, and found that rs1682111 risk allele A boosted the risk of BC risk, as a risk factor for breast cancer occur (Zhang et al, ). In the study of colorectal cancer, also found that ACYP2 gene promoted the occurrence of colorectal cancer, for colorectal cancer, rs843645 is also a risk factor (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%